Undiagnosed Ectopic Pregnancy among Unsupervised use of Medical Abortion pills - Joshi, Arun Prasad; Chitrakar, NS; Pariyar, J; Shrestha, I; Maharjan, R; Maharjan, P (Nepal Journal of Obstetrics and Gynaecology, 2017)
Aims: To identify and share the experience of clinical presentation and management of ectopic pregnancy (EP) in women who presented with unsupervised use of Medical abortion (MA) pills. Methods: A prospective study was conducted in department of Obstetrics and Gynaecology of Civil Service Hospital over one year (March 2015- February 2016). Women with a history of unsupervised use of MA pills were taken into study group as there has been a trend of taking theses pills without consultation in recent days. Detail clinical, menstrual, obstetrics and MA history were taken. Relevant investigations and Ultrasonography were done. Women diagnosed to have ectopic pregnancy were followed and their operative findings were recorded. Results: Ninety-six women presented with unsupervised use of MA, among which 8 (8.33%) diagnosed to have EP. Most women were 20-30 years of age and 37.5% were unmarried. They gave history of taking MA from pharmacy. Among eight women, 37.5 % had taken MA at the period of gestation <5 weeks, 37.5% between 5-7 weeks and 25% >7-9 weeks. Fifty percent attended hospital after seventy- two hours of MA. Majority (50%) presented with lower abdominal pain and ruptured EP with hemoperitoneum (>one litre) requiring blood transfusion. History of easy availability and social reasons for MA intake were given by 37.5% each. Conclusions: Even though medical abortion is easily accessible, affordable and available, it should also be safer. It is of utmost importance to take it from health facility or a registered medical practitioner following World Health Organization (WHO) guidelines, one of which is excluding extra-uterine pregnancy.